2017
DOI: 10.2174/1570179413666160831124749
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Polyurethane and its Polymer Composites

Abstract: In the recent years, the research about polyurethane (PU) composites (thermoplastic, thermoset, biobased polyurethane with synthetic fibers (glass, aramid and carbon) and natural fibers used as reinforcement of polymers has been increased due to their biodegradability, lightness, reduced cost and favorable mechanical properties. Unique mechanical, thermal, and chemical properties of Polyurethanes (thermoset/thermoplastic) can be designed by the reaction of various polyhydric compounds (polyols) and polyisocyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 0 publications
0
39
0
2
Order By: Relevance
“…Eco-grade TPU is a new class of elastomer which is produced from renewable source with a content of 46% of total mass. The novel polyurethane based eco-composites can be fabricated using natural fibers with this new grade of polyurethane elastomer (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Eco-grade TPU is a new class of elastomer which is produced from renewable source with a content of 46% of total mass. The novel polyurethane based eco-composites can be fabricated using natural fibers with this new grade of polyurethane elastomer (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of a novel biodegradable and biocompatible polyurethane material is important for biomedical engineering applications. Different kinds of polyurethanes are widely used in biomedical applications due to their biostability, biodegradability, and tunableness of the chain-segment structure from an extensive range of available raw materials, such as long chain diols, diisocyanates, and short chain diols (chain extenders) [3][4][5]. It is well-known that conventional polyurethane is composed of soft segments and hard segments.…”
Section: Introductionmentioning
confidence: 99%
“…For each application, the PU compositions selected afford needed physical characteristics that may be uniquely required in the particular application. Therefore, the research on PU has been a hot topic in polymer research [ 6 8 ]. Previous investigations have shown that the relationship between structure and properties in PUs is of course largely determined by selection of starting materials, but also by the polymerization method [ 9 , 10 ], degree of phase separation [ 11 , 12 ], morphology [ 13 , 14 ] and by extent of crystallization [ 15 , 16 ] and hydrogen bonding [ 17 , 18 ] that are present in the final polymer.…”
Section: Introductionmentioning
confidence: 99%